Isometric posterior chain peak force recovery response following match-play in elite youth soccer players: associations with relative posterior chain strength - Constantine, E.; Taberner, M.; Richter, C.; Willett, M.; Cohen, D. D. (Sports, 2019)
The purpose of this study was to determine changes in two tests of lower limb isometric posterior chain force (IPC-F) following 90 min of match-play in elite youth soccer players and the interaction between relative strength and recovery profile. 14 players (age: 16 ± 2 years) performed 3 × 3 second IPC-F tests unilaterally at 30° and 90° of knee and hip flexion pre- and post-match, +24 h, +48 h, and +72 h post-match. Peak force was recorded for both limbs, combined and expressed relative to bodyweight (N/kg). A two-way repeated measures analysis of variance was performed to determine differences in force output between joint angles, time intervals and subjects. As there was no interaction between angle and time (p = 0.260), we report the change between timepoints as mean Delta in 90° + 30° IPC-F. Relative to pre-match IPC-F, there were significant decreases post (Delta = -18%; p > 0.001) and at +24 h (Delta = -8%; p = 0.040), no significant difference at +48 h (Delta = 0%; p = 0.992) and a significant increase at +72 h (Delta = +12%; p = 0.005). There was a large inter-individual variability in recovery profile at both angles and substantial differences between post-match deficits at 90° (-10.8%) compared to 30° (-20.7%). Higher pre-match IPC-F was correlated with the magnitude of IPC-F deficits at both angles and all time points (r = 0.56 to 0.70, p = < 0.01) except for post-match 90°. Regular IPC-F monitoring to determine the magnitude of match-induced fatigue and track recovery may help inform decision-making regarding modifications to individual players training load, particularly as there is a large inter-individual variability in response to competition. Further research is warranted to better understand and address the finding that stronger players showed larger force deficits and slower recovery following match-play.